Agent based resource brokering and allocation in wireless grids : revisited. - Sedaghat, Mina; Othman, Mohamed (2009)
Existing internet frameworks, like grids, wireless grids, P2P networks are now provide effective channels for gathering and processing widespread information, using the available resources within reasonable cost. Agent technology emerges as a suitable solution to combine with these frameworks for covering the existing challenges, like discovery, load balancing and resource management. Although different models introduced, practical solutions remain elusive and tend to exhibit underlying conflicts between different paradigms. This paper, aimed to revisit and discuss the characteristics on one of these system architectures based on agents. The base model is introduced, then our re-experiment is described and the results are compared, such that the challenges on this agent base model is highlighted and new ideas can be applied.